2021
DOI: 10.4038/jccpsl.v27i2.8392
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causative Organisms of Asymptomatic Bacteriuria among Pregnant Women in Karachi, Pakistan

Abstract: Introduction: During pregnancy, urinary tract experiences various anatomical as well as physiological changes which lead to the development of urinary tract infections. Of these, asymptomatic bacteriuria is prevalent during pregnancy and the adverse outcomes could include intrauterine growth retardation, pyelonephritis, preterm delivery, low birth weight, hypertension, and anaemia. Hence, screening for asymptomatic bacteriuria should be included in antenatal care. Objectives:To determine the prevalence of asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Schmiemann et al 26 also reported that E. coli caused most of the cases of complicated and uncomplicated UTI. In a study among pregnant women in Pakistan by Tabinda et al 27 the most common cause of asymptomatic bacteriuria was also E. coli followed by Klebsiella and Staphylococcus spp. These are similar to what was found in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Schmiemann et al 26 also reported that E. coli caused most of the cases of complicated and uncomplicated UTI. In a study among pregnant women in Pakistan by Tabinda et al 27 the most common cause of asymptomatic bacteriuria was also E. coli followed by Klebsiella and Staphylococcus spp. These are similar to what was found in our study.…”
Section: Discussionmentioning
confidence: 95%
“…10,11 However, even higher gures were quoted from Saudi Arabia (32.1%) Iraq (42.9%) and Nigeria (37.1%). 12,13,14 Frequency as low as 3.3% has been quoted from India. 15 16,17,18,19 Another study has shown an upward trend of ASB among multiparous women of advanced age.…”
Section: Variablesmentioning
confidence: 99%